Contrasting Nav1.8 Activity in Scn10a−/− Ventricular Myocytes and the Intact Heart. Issue 11 (2nd November 2016) - Stroud, Dina Myers; Yang, Tao; Bersell, Kevin; Kryshtal, Dymtro O.; Nagao, Satomi; Shaffer, Christian; Short, Laura; Hall, Lynn; Atack, Thomas C.; Zhang, Wei; Knollmann, Bjorn C.; Baudenbacher, Franz; et al.
Abstract : Background: Genome‐wide association studies have implicated variants in SCN10A, which encodes Nav1.8, as modulators of cardiac conduction. Follow‐up work has indicated the SCN10A sequence includes an intronic enhancer for SCN5A . Yet the role of the Nav1.8 protein in the myocardium itself is still unclear. To investigate this, we use homozygous knockout mice ( Scn10a −/− ) generated by disruption of exons 4 and 5, leaving the Scn5a enhancer intact. Methods and Results: We previously reported that pharmacologic blockade of Nav1.8 in wild‐type animals blunts action potential prolongation by ATX‐II at slow drive rates (≤1 Hz). Here we present evidence of the same blunting in Scn10a −/− compared to wild‐type ventricular myocytes, supporting the conclusion that Nav1.8 contributes to late sodium current at slow rates. In contrast to earlier studies, we found no differences in electrocardiographic parameters between genotypes. Low‐dose ATX‐II exposure in lightly anesthetized animals and Langendorff‐perfused hearts prolonged QTc and generated arrhythmias to the same extent in wild‐type and Scn10a −/− . RNA sequencing failed to identify full‐length Scn10a transcripts in wild‐type or knockout isolated ventricular myocytes. However, loss of late current in Scn10a −/− myocytes was replicated independently in a blinded set of experiments. Conclusions: While Scn10a transcripts are not detectible in ventricular cardiomyocytes, gene deletion results in reproducible loss of late sodium current under extreme experimental conditions. However, there are no identifiable consequences of this Scn10a deletion in the intact mouse heart at usual rates. These findings argue that common variants in SCN10A that affect ventricular conduction do so by modulating SCN5A .